RESIDUAL LIFE ASSESSMENT AND LIFE EXTENSION OF SUBWAY CARS - Trietiakov, A. V.; Borisov, S. V. (Science and Transport Progress, 2004)
The paper reports the main results of work carried out to prolong service life of underground cars: analysis of failures found in the process of technical diagnostics of car body shells and frames and development of the design to eliminate the failures.